Niemann-Pick disease type A: a case report - Mirani, Erna; Pratiwi, Rina; Widyastiti, Nyoman Suci; Ekowati, Liana; Mexitalia, Maria (Medica Hospitalia : Journal of Clinical Medicine, 2021)
BACKGROUND Niemann-Pick disease (NPD) types A result from the deficient activity of sphingomyelinase. NPD type A is characterized by early-onset, progressive neurodegenerative course; systemic disease manifestations, including massive hepatosplenomegaly, interstitial lung disease, and cherry-red macula; and death in early childhood. The objective: to enhance the recognition of health care providers about the potential undiagnosed NPD because nonspecific clinical manifestation CASE PRESENTATION A 18-months-old boy was admitted to Dr. Kariadi Hospital with enlarged abdomen since seventh month old with failure to thrive. He also showed progressive loss of neurologic function, microcephaly with open major fontanelle, recurrent pulmonary and systemic infection. Physical examination revealed facial dysmorphic, milestone regression, under-nutrition, crackles in both lungs, hepatosplenomegaly with petechial in extremities and floppy infants. Laboratory investigations showed anemia (9.4 g/dL) and thrombocytopenia (73.000/mm3). The lactate dehydrogenase (482 U/L) and alkaline phosphatase (159, 03 IU/L) were higher than normal. Abdominal ultrasound revealed hepatomegaly with normal parenchyma and splenomegaly without nodule. Skeletal survey revealed Erlenmeyer flask deformity. Foam cell are detected in bone marrow puncture. Retcam examination showed cherry red spot at the macula. Bera revealed auditory neuropathy. The enzyme activity showed normal ?–Glucosidase (5.55 uM/hr) and chitotriosidase (105,8 nmol/ml) but low sphingomyelinases activity (0.30 uM/hr) which confirmed the diagnosis of NPD. DISCUSSION Niemann-Pick disease (NPD) types A result from the deficient activity of sphingomyelinase. NPD type A is characterized by early-onset, progressive neurodegenerative course; systemic disease manifestations, including massive hepatosplenomegaly, interstitial lung disease, and cherry-red macula; and death in early childhood. Type A is very rare and a severe infantile form with neurologic degeneration resulting in death usually by 3 years of age. No treatment available for type A and It’s a rare disease in Indonesia. CONCLUSION These investigations were able to diagnose this child as a NPD-Type A. Patient was closely monitored and symptomatic treatment was provided.